Optimization of a diagnostic algorithm for benign breast nodules - T. E. Usmanova; F. N. Il’chenko; A. S. Filatov; A. V. Kubyshkin (Опухоли женской репродуктивной системы, 2016)
The results of examinations were studied in 76 reproductive-aged patients with benign breast nodules (BBNs). The determination of the leukocyte common antigen CD45 in the trephine biopsy specimens, as well as proteinase activity in the solid tumor homogenates and in the cyst puncture samples in the preoperative stage or the postpuncture period can identify groups of patients with BBNs in relation to a tissue inflammatory response. BBNs with a tissue inflammatory response showed increases in the level of nonspecific proteinases and in the expression of the leukocyte common antigen CD45, which was accompanied enhanced proliferative activity (Ki-67) and elevated levels of apoptosis proteins (p53 and Bcl-2), and estrogen and prolactin receptors.